Penggunaan Tepung Brangkasan Ubi Jalar (Ipomoea batatas L.) Terfermentasi Dalam Ransum Terhadap Recahan Karkas Ayam Kampung Super Umur 10 Minggu - Yohanes Oktavianus Katu; I Nyoman Kaca; Luh Suariani (GEMA AGRO, 2021)
Super free-range chicken which is currently a very lucrative new business opportunity because the demand for free-range chicken has increased significantly due to high consumer demand. The type of agricultural waste that can be used as ration material is sweet potato stove. The purpose of this study was to determine the effect of the use of fermented sweet potato stover flour in the ration on the carcass crumbs of super free-range chicken aged 10 weeks, to find out what percentage of the level of use of fermented sweet potato stover flour in the ration that was able to provide the best results on the super-fried free-range chicken carcass. 10 weeks old. The research design used was a completely randomized design (CRD) which consisted of 5 treatments, namely: R0 (without the addition of sweet potato stover flour), R1 (addition of non-fermented sweet potato stover flour 3%), R2 (addition of fermented sweet potato stover flour 3), %), R3 (addition of fermented sweet potato stover flour 6%), R4 (addition of 9% fermented sweet potato stover flour). Each treatment was repeated 3 times. The use of sweet potato stover flour in the ration had no significant effect (P>0.05) on carcass weight, thigh weight, chest weight, back weight and wing weight. The use of sweet potato stover flour in the ration tends to be higher at the 3% level of fermented sweet potato stover flour, but it does not give a significant effect.